STRATEGI KOMUNIKASI PEMBANGUNAN UPT. PASAR CIK PUAN KOTA PEKANBARU DALAM MEMPERTAHANKAN EKSISTENSI PASAR TRADISIONAL - Muhammad Arif; dede yochi (LPPM Universitas Abdurrab, 2023)
The presence of modern markets is considered by various groups to have cornered the existence of traditional markets. This type of market is a market where merchandise is traded at the right price so there is no bargaining activity. This study used a qualitative method using the Cultip and Center communication strategy theory with data collection techniques by means of interviews, observation and documentation. The research subjects were UPT Cik Puan Pekanbaru's communication strategy and the object of research was UPT Pasar Cik Puan Pekanbaru. The results of this study are the fact that there is currently a decrease in visitors to traditional markets. This is caused by several factors such as infrastructure development that has not been completed. the planning that will be carried out by UPT Pasar Cik Puan Pekanbaru is to continue to synergize with Pemko and related parties to continue building the market which is currently still neglected, then the UPT Pasar Cik Puan Pekanbaru also provides education to traders who work with BPOM about food hygiene. in the Cik Puan market in Pekanbaru. Communication established by UPT Cik Puan Pekanbaru market is with the government of Pekanbaru City to follow up on the construction of Cik Puan Pekanbaru market. The current evaluation carried out by UPT Pasar Cik Puan Pekanbaru is more about educating traders and evaluating development plans